Ending the HIV Epidemic for Persons Left Behind in the Advances of HIV: Intervention Studies Addressing the HIV Continuum of Care. (February 2023) - Metsch, Lisa R.; Feaster, Daniel J.; Parish, Carrigan L.; Gooden, Lauren K.; Matheson, Tim; Pereyra, Margaret R.; Tross, Susan; Haynes, Louise; Rodriguez, Allan; Tookes, Hansel; Das, Moupali; Colasanti, Jonathan; et al.
The advent of antiretroviral therapy and biomedical prevention has transformed HIV from a fatal disease to a chronic condition where people with HIV (PWH) can live long, healthy lives. Yet, there remains a subset of PWH left behind from receiving timely HIV diagnosis and care. Striking inequalities in access to resources, socioeconomic disparities, and social forces have prevented certain PWH from achieving significant health and quality of life (QOL) improvements experienced by those who secure life-saving treatment. For decades, our multidisciplinary team developed a collaborative scientific portfolio focused on helping those left behind advance along the HIV continuum of care. In this manuscript, we highlight some of our U.S.-based social interventions that have addressed the disparities and sub-optimal QOL encountered by overlooked populations with the goal of achieving timely HIV diagnosis, care, and sustained viral suppression. We then outline our many lessons learned and vision for the next crucial steps ahead.